Implementasi Kampung Keluarga Berencana Di Kabupaten Badung Provinsi Bali - Made Agus Sugianto (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2021)
The rapid population growth will lead the general conflicts in social life of social life. One of the family planning programs that are managed and organized, by and for the community is the Family Planning Village program. This study aims to evaluate the implementation of the Family Planning Village program in Badung Regency Bali Province. The method used in this research is descriptive-analytic with Desk Study design in June and July 2019. The results show that the implementation of the Kampung KB program has better done well. Indicators of Contraceptive Prevalence Rate, Percentage of Long-Term Contraceptive Method, Number of Unmet Needs, and Percentage of First Marriages of Women aged less than 21 years have reached the set target, likewise the percentage of new family planning acceptors in KB Kampung in Badung Regency has increased from 10% in 2016 to 12% in 2018. To optimize the achievement of the implementation of the Kampung KB program in the Badung Regency, the Badung Regency Government needs to strengthen the KB village institution, improve family empowerment programs and build information technology-based management systems so that data and information are available quickly and accurately.